Enhancing early childhood literacy through the habit of shared storybook reading at TK Mutiara Hati Tangerang - Nurhillal, Zahroh; Utami, Fitria Budi; Valentin, Adelia Dwi; Ningsih, Tia Indriani (Universitas Muhammadiyah Magelang, 2025)
This community service program aimed to enhance early childhood literacy through the practice of shared storybook reading. The activities were conducted at TK Mutiara Hati, Tangerang, involving 35 students and 14 teachers. The methods employed included read-alouds, literacy games, and a hands-on practice of creating simple storybooks using stickers and pictures. The results showed a significant improvement in the children's literacy skills. A total of 30 children (85%) demonstrated enhanced ability to comprehend and retell story content. Children in this category were able to participate actively, for instance, in